Finite element simulation of anti-stab mechanism of aramid flexible composites - WANG Ruining; HOU Xiao; ZHANG Yajuan; JIA Xiaoya (Xi'an Gongcheng Daxue xuebao)
In order to predict the anti-stabbing performance of aramid flexible composite and to investigate the basic law of the response of aramid flexible composites to knife penetration, aramid flexible composites were prepared by impregnation with multi-phase shear thickening solution and coating with silicon carbide/thermoplastic polyurethane as well as extraction and quasi-static stabbing experiments. Finite element simulations of a single-layer quasi-static knifed aramid composite model and a multi-layer dynamic knifed aramid composite model were established by refining the friction coefficients, and Python script was used to effectively simplify the modeling process to investigate the anti-knife stabbing mechanism of aramid flexible composites. The results show that the friction coefficient between yarns of the silicon carbide/thermoplastic polyurethane coated aramid composites is the highest. The friction coefficient between yarns impregnated with shear thickening solution is good and does not limit yarn stretching deformation, and has good anti-stabbing property. The main failure mode of multi-layer aramid fabric during dynamic puncture process is yarn breakage and yarn deformation is less. The establishment of the model can provide a reference for fast and accurate prediction of the anti-stabbing properties of flexible composites.